Dampak Media Pembelajaran Articulate Storyline Terhadap Hasil Belajar Bahasa Inggris Siswa - Nurindah Nurindah (CV. Rayyan Dwi Bharata, 2025)
The research was conducted to determine the effect of the use of Articulate Storyline Based Learning Media on student learning outcomes in English Subject at MTSS Pabbambaeng Bulukumba. Thesis Educational Technology Study Program. The purpose of this study was determine the effect of using learning media by utilizing Articulate Storyline-based media. This research is a quantitative research using an experimental with a pre-experimental research design, namely one group pretest posttest design. The source of data in this study is primary data obtained by direct observation and observation by researchers. The results of this study state that through Articulate Storyline-based learning media in learning can have an influence on student learning outcomes in English Subject Class VII A at MTSS Pabbambaeng Bulukumba and give a positive respons to the learning media.